The Nuclear Ban Treaty and 2018 Disarmament Forums: An Initial Impact Assessment - Michael Hamel-Green (Journal for Peace and Nuclear Disarmament, 2018)
The July 2017 UN Treaty on the Prohibition of Nuclear Weapons (TPNW) will come into force when 50 UN Member States ratify it. The new treaty has been condemned by nuclear weapon states on the grounds of its claimed adverse impacts on Non-Proliferation Treaty (NPT), and for not taking account of progress through step-by-step incremental measures. Supporters of the new treaty, including 122 UN Member states, have been concerned about the lack of substantive nuclear disarmament progress as envisaged under Article VI of the NPT. This study analyses the arguments for and against the new treaty in the context of recent 2018 NPT and Conference on Disarmament (CD) sessions, and regional nuclear disarmament arrangements. It draws upon the discussions and debates at the Geneva 23 April–4 May 2018 NPT Preparatory Committee, and positions taken in the 2018 CD sessions, to assess immediate and potential longer-term impacts of the TPNW. The roles of regional measures nuclear-weapon-free zones (NWFZs) and weapon-of-mass-destruction-free zones (WMDFZs) are also considered in the context of the TPNW and the NPT. The study argues that the TPNW, through its normative delegitimation and stigmatisation of nuclear weapons, is already creating a discernible impetus for substantive nuclear disarmament within and beyond the NPT and CD forums, despite the present resistance mounted by the nine nuclear-armed states.